Pengembangan E-Modul Interaktif Berbantuan Flipbook pada Materi Daerahku dan Kekayaan Alamnya untuk Meningkatkan Hasil Belajar Kelas IV - Siti Zulaikha; Elly Sukmanasa; Desti Herawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The increasing integration of digital technology in education demands teaching materials that are interactive and responsive to students' learning needs, yet many primary schools still rely on printed textbooks that limit student engagement. This study aims to develop an interactive e-module assisted by Flipbook covering the topic "My Region and Its Natural Wealth," determine the product's feasibility, test its effectiveness in improving student learning outcomes, and assess teacher and student responses to the developed product. The study employs a Research and Development (R&D) approach using the ADDIE model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 31 students from class IV-A at SDN Mekarsari 6, Depok City, during the 2025/2026 academic year. Data were collected through observation, interviews, expert validation, teacher and student response questionnaires, as well as pre-tests and post-tests. Data were analyzed using descriptive quantitative methods, specifically the N-Gain test and the Wilcoxon Signed Rank Test. The results indicate that the e-module achieved a "highly feasible" rating based on assessments by media experts (92.5%), language experts (95%), material expert 1 (89%), and material expert 2 (90%), with an overall average of 91.63%. Teacher responses yielded a 96% rating and student responses 98.93%, both in the "excellent" category. Student learning outcomes improved from an average pre-test score of 78 to an average post-test score of 91.07, with an N-Gain score of 0.5323, indicating a moderate level of improvement. The Wilcoxon Signed Rank Test showed Asymp. Sig. (2-tailed) = 0.000 < 0.05, confirming a significant difference in learning outcomes before and after using the e-module. Thus, the Flipbook-assisted interactive e-module is feasible and effective as a teaching resource for enhancing student learning outcomes in IPAS lessons at the primary school level.